Mechanistic insight into the destabilization of p53TD tetramer by cancer-related R337H mutation: a molecular dynamics study. Issue 8 (15th February 2022) - Yu, Yawei; Dong, Xuewei; Tang, Yiming; Li, Le; Wei, Guanghong
Abstract : Cancer-related R337H mutation disrupts the salt bridge, π–π stacking and hydrophobic interactions, and thus induces destabilization of the p53TD tetramer. Abstract : The p53 protein is a tumor suppressor crucial for cell cycle and genome integrity. In a very large proportion of human cancers, p53 is frequently inactivated by mutations located in its DNA-binding domain (DBD). Some experimental studies reported that the inherited R337H mutation located in the p53 tetramerization domain (p53TD) can also result in destabilization of the p53 protein, and consequently lead to an organism prone to cancer setup. However, the underlying R337H mutation-induced structural destabilization mechanism is not well understood. Herein, we investigate the structural stability and dynamic property of the wild type p53TD tetramer and its cancer-related R337H mutant by performing multiple microsecond molecular dynamics simulations. It is found that R337H mutation destroys the R337–D352 hydrogen bonds, weakens the F341–F341 π–π stacking interaction and the hydrophobic interaction between aliphatic hydrocarbons of R337 and M340, leading to more solvent exposure of all the hydrophobic cores, and thus disrupting the structural integrity of the tetramer. Importantly, our simulations show for the first time that R337H mutation results in unfolding of the α-helix starting from the N-terminal region (residues 335 RER(H)FEM 340 ). Consistently, community network analyses reveal that R337H mutation reduces dynamical correlation and global connectivity of p53TD tetramer, which destabilizes the structure of the p53TD tetramer. This study provides the atomistic mechanism of R337H mutation-induced destabilization of p53TD tetramer, which might be helpful for in-depth understanding of the p53 loss-of-function mechanism.